Transcriptional and translational expression of PPARY in the human colorectal cancer dell llne, colo 205 - Yaacob, Nik Soriani (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Peroxisome proliferator-activated receptors (PPARs) are ligand-dependent transcription factors of the nuclear hormone receptor superfamily that includes the receptor for steroid, retinoid and thyroid hormone. These nuclear receptors are characterised by their ability to bind to specific DNA sequences and, when activated by a ligand, PPARs regulate the expression of various genes and their functions (Auwerx 1999; Vamecq eta/., 1999). PPAR was first cloned from the mouse liver by lsseman and Green in 1990. The PPAR family consists of three distinct isoforms, namely PPARa, PPARB (or PPARf3) and PPARy. Each isoform is encoded by a separate gene (Tontonoz eta/. 1994). PPARy is further divided into the PPARy1, PPARy2, PPARy3 and PPARy4 isoforms (Sundvold and Lien, 2001) whereby PPARy2 has an additional30 amino acids at its N-terminus but is believed to have similar functions as those of PPARy1 (Sundvold eta/. 1995). PPARy3 is only found in humans and the expressed protein is identical to that of PPARy1 (Fajas eta/., 1998). PPARy is found mainly in adipocytes and cells of the immune system (Braissant et a/1996; Lemberger et a/ 1996) and is involved in the regulation of adipogenesis, glucose metabolism and macrophage development and function (reviewed in Kersten eta/., 2000). PPARr and carcinogenesis Although it has long been known that PPARa ligands such as hypolipidaemic drugs cause hepatocarcinogenesis in rodents (Reddy and Chu 1996), the possible involvement of PPAR in human neoplasms has only recently emerged. PPARy has been shown to be expressed in human colon cancer (Sarraf eta/., 1998), prostate cancer (Mueller eta/., 2000) and breast cancer (Clay eta/., 1999) cell lines. However the involvement of PPARy activity in inducinggrowth inhibition in such tumours have been contradictory. For example, it has previously been shown that PPARy can inhibit the proliferation of human colorectal carcinomas (Brockman eta/., 1998). In sharp contrast with this, however, was the report that activation of PPARy promotes the development of colon tumors in C57BU6J-APCMin/+mice (Lefebvre et at., 1998), a clinically relevant model for both human familial adenomatous polyposis and sporadic colon canc~r (Suet~/., 1992). Recent evidence suggests that PPARy ligands could have an anti-tumor effect in human$ as these compounds decrease cell growth and induce apoptosis in several malignant human cell types, including colorectal carcinomas (S~rraf eta/., 1998). Specific ligands of PPARy such as the antidiabetic thiazolidinediones (TZDs), natural fatty acid derivatives, non-steroidal anti-inflammatory drugs (NSAIDs) and certain polyunsaturated fatty acids have been identified (Palmer et a/., 1998). In agreement with the potential role of PPARy ligands for the treatment of cancer, our present study was aimed at observing the growth inhibition of the colorectal cancer cell line, COL0205 by the PPARy ligand, ciglitazone. This aim was slightly different from the original one proposed under this grant whereby the determination of both PPARa and PPARy expression by two colorectal cell lines, HT-29 and COL0205 was proposed. The change was necessary because the amount of funds approved was about 45% less than that requested and also based on current developments in this research area including the use of a more advanced technique of gene quantification, namely, using real time PCR. In addition, we propose to correlate these findings with the expression of the corresponding proteins by the cell line.